Analysis of Training Effectiveness of Handloom Weaving and Value Addition - Deo, Sangeeta; Sarkar, Smriti Rekha; Sil, Animesh (Indian Journal of Extension Education, 2010)
The handloom sector is the second largest employer in India. Government of India is committed to develop this sector as it is a source of livelihood of rural people. There are many Government schemes and assistance for this sector. So proper training in handloom weaving and value addition is needed to take up. Handloom weaving as an entrepreneur department of Textile and Apparel Designing has organized a training on handloom weaving and value addition. To see the impact of training, an effectiveness analysis study was conducted purposively. The pre-post research design method was used to find out gain in knowledge, change in attitude and skill performance of the respondents. Majority of the respondents were in the middle age group. Sixty percent of the respondents were having education upto middle school. There was significant increase in the level of knowledge, attitude and skill performance of the respondents after the training. Eighty per cent of the respondents had low level of knowledge before the training and after the training only 6.6 per cent had low level of knowledge and 26.6 per cent had acquired high level of knowledge. Majority of the respondents had acquired high level of skill performance. Thirty per cent of the respondents unfavourable attitude changed into the most favourable attitude after the training.